Interplay of stress responses in mungbean cultivars subjected to combined exposure to Macrophomina phaseolina infection and drought stress - Kaur, Sahib; Kumari, Nilima; Sharma, Vinay (Plant stress (Amsterdam), 2024)
•The combined stress tolerance and susceptibility was subject to the type of mungbean cultivar under consideration and varied depending upon the changing environmental conditions.•The plants previously exposed to drought stress performed exceptionally better in terms of yield and nutritional quality when subjected to M. phaseolina infection.•Better defense response in plants exposed to the combined DF (drought-fungus) and FD (fungus-drought) treatment was attributed to increased callose deposition, and proline and soluble sugar levels respectively.•Already stressed plants switch their response strategies on encountering another sequential stress condition. The increased frequency of dry spells related to climate change has posed a major threat to food security globally. Recently, a surge has been observed in the disease incidences caused by the phytopathogens that flourish under hot and dry conditions. Macrophomina phaseolina is one such pathogen that can cause an absolute loss of productivity in host plants including Vigna radiata (mungbean). In the current study, six mungbean cultivars were screened for the combined stress caused by simultaneous exposure to M. phaseolina infection and drought. Both the drought stress (D) and M. phaseolina infection (F) were applied to ten days old plants in three combinations i.e. DF (one week drought stress followed by fungal infection and normal watering), DFD (one week drought stress followed by fungal infection with extended drought) and FD (normally watered plants exposed to fungal infection followed by drought stress). The growth, physiological (photosynthetic efficiency) and biochemical parameters (antioxidant enzyme activity, callose, soluble sugars, proline, lipid peroxidation and hydrogen peroxide content) were recorded in one month old mungbean plants. The yield and nutritional quality of seeds were also determined. The data revealed that the cultivar RMG-975 consistently maintained the yield under all the stress conditions; the maximum decrease (19.1%) was recorded in the total seed weight of phytopathogen inoculated plants. With 60.6% increase in mean variability in yield (weight of seeds) under DF treatment, the cultivars (except ‘SML-668′) previously exposed to drought stress performed exceptionally better in terms of nutritional quality (increase in mean variability of seed protein-26.45% and total antioxidant capacity-14.84%) when subjected to M. phaseolina infection. Therefore, the strategy of short-term drought stress followed by the application of an elicitor that mimics the induction of biotic stress response could be opted for the increased production of seeds rich in protein and antioxidants. The combined stress tolerance and susceptibility was subject to the cultivar type and varied with the changing environmental conditions. The increased resistance under DF was attributed to callose deposition whereas under FD, it was due to higher accumulation of proline and soluble sugars. The increase in mean variability in proline (drought stress marker) levels under FD (133.41%) and DFD (21.25%) and reduction under DF treatment (39.75%) showed that already stressed plants switch their response strategies on encountering another sequential stress condition. [Display omitted]